Zinc Transport Differs in Rat Spermatogenic Cell Types and Is Affected by Treatment with Cyclophosphamide. Issue 1 (1st July 2016) - Downey, Anne Marie; Hales, Barbara F.; Robaire, Bernard
Abstract: Adequate zinc levels are required for proper cellular functions and for male germ cell development. Zinc transport is accomplished by two families of zinc transporters, the ZIPs and the ZnTs, that increase and decrease cytosolic zinc levels, respectively. However, very little is known about zinc transport in the testis. Furthermore, whether cytotoxic agents such as cyclophosphamide (CPA), a known male germ cell toxicant, can affect zinc transport and homeostasis is unknown. We examined zinc transporter expression and zinc transport in pachytene spermatocytes (PS) and round spermatids (RS) in a normal state and after exposure to CPA. We observed differences in the expression of members of the ZnT and ZIP families in purified populations of PS and RS. We also observed that RS accumulate more zinc over time than PS. The expression of many zinc binding genes was altered after CPA treatment. Interestingly, we found that the expression levels of ZIP5 and ZIP14 were increased in PS from animals treated daily with 6 mg/kg CPA for 4 wk but not in RS. This up-regulation led to an increase in zinc uptake in PS but not in RS from treated animals compared to controls. These data suggest that CPA treatment may alter zinc homeostasis in male germ cells leading to an increased need for zinc. Altered zinc homeostasis may disrupt proper germ cell development and contribute to infertility and effects on progeny.